The Effect of Sociocultural Factors on Maternal Short Psychiatric Status and Hyperemesis Gravidarum - Mehmet Baki Şentürk; Yusuf Çakmak; Mehmet Şükrü Budak (Medical Network, 2016)
OBJECTIVE: This study sought to investigate the associations between Hyperemesis Gravidarum and both sociocultural factors and psychiatric status. STUDY DESIGN: A prospective non-randomized cohort design was employed. A total of 79 patients with Hyperemesis Gravidarum and 71 healthy pregnant women were enrolled. The study and control groups were compared according to results on the Brief Psychiatric Rating Scale and sociocultural factors specific to the region. RESULTS: Anxiety, somatic concern, tension, depressive mood, hostility, motor retardation, uncooperativeness and blunted effect were found to be statistically significantly higher in patients with Hyperemesis Gravidarum(p<0.01 and p<0.05). Furthermore, pregnant women living in extended families had statistically higher anxiety scores than those residing in nuclear families (p<0.05). CONCLUSION: Psychiatric status as well as sociocultural factors specific to the society in which the individuals live should be taken into account in assessments of patients with Hyperemesis Gravidarum.